Convective and Advective Heat Transfer in Geological Systems - Zhao, Chongbin; Hobbs, Bruce E.; Ord, Alison (Advances in Geophysical and Environmental Mechanics and Mathematics, 2008)
This monograph aims to provide state-of-the-art theoretical results in a systematic treatment of convective and advective heat transfer during fluid flow in geological systems at the crustal scale. Although some numerical results are provided to complement theoretical ones, the main focus of this monograph is on theoretical aspects of the topic. The theoretical treatment contained in this monograph is also applicable to a wide range of problems of other length-scales such as engineering length-scales. To broaden the readership of this monograph, common mathematical notations are used to derive the theoretical solutions. This enables this monograph to be used either as a useful textbook for postgraduate students or as a valuable reference book for mathematicians, engineers and geoscientists.